Helicobacter pylori infection selectively attenuates endothelial function in male mice via exosomes-mediated ROS production - Zhang, Linfang; Xia, Xiujuan; Wu, Hao; Liu, Xuanyou; Zhu, Qiang; Wang, Meifang; Hao, Hong; Cui, Yuqi; Li, De-Pei; Chen, Shi-You; Martinez-Lemus, Luis A.; Hill, Michael A.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Substantial sex differences exist in atherosclerosis. Excessive reactive oxygen species (ROS) formation could lead to endothelial dysfunction which is critical to atherosclerosis development and progression. Helicobacter pylori (H. pylori) infection has been shown to attenuate endothelial function via exosomes-mediated ROS formation. We have demonstrated that H. pylori infection selectively increases atherosclerosis risk in males with unknown mechanism(s). The present study was to test the hypothesis that H. pylori infection impaired endothelial function selectively in male mice through exosome-mediated ROS formation. H. pylori infection attenuated acetylcholine (ACh)-induced endothelium-dependent aortic relaxation without changing nitroglycerine-induced endothelium-independent relaxation in male but not female mice, associated with increased ROS formation in aorta compared with controls, which could be reversed by N-acetylcysteine treatment. Treatment of cultured mouse brain microvascular endothelial cells with exosomes from H. pylori infected male, not female, mice significantly increased intracellular ROS production and impaired endothelial function with decreased migration, tube formation, and proliferation, which could be prevented with N-acetylcysteine treatment. The results suggested that H. pylori infection selectively impairs endothelial function in male mice due to excessive exosomes-mediated ROS formation.